Clinical Pharmacist in Nuclear Medicine: A New Role in Ascendancy - Patel, Jyoti; Bhatt, Sandipkumar (Indian Journal of Pharmacy Practice)
Nuclear pharmacy is a unique branch of pharmacy services that focuses on the proper, safe management and use of radiopharmaceuticals. Most of pharmacist spent their time in traditional services while few renders clinical services in hospital setting even recruitment and regulatory body also demand undergraduate qualification which may find insufficient to render services. It is a matter of question how many provides clinical or pharmaceutical care? But spending a time in clinical activities by pharmacist is an issue of debate. After satisfactory completion of project in this area, attempt has been made by this article to explore our perception on scope, education and functions of pharmacist especially by hospital and by clinical pharmacist. How pharmacist can perform pharmaceutical care in this unique service area is discussed and responsibilities of pharmacist in nuclear pharmacist are proposed.
Keywords: Nuclear medicine; clinical pharmacy; radiations; pharmaceutical care